Suggested activities on magnetism using an improvised current balance apparatus - Pilapil, Yvonne A. 1948- (1978)
The researcher maintained the idea that if physics is to be taught effectively, students should be able to visualize and concretize the physical laws. As a guiding principle, a current balance is a device that measures the magnetic force between two parallel current-carrying conductors. Through this principle, activities were developed to test the effectiveness of the improvised apparatus. The students showed enthusiasm while performing the different activities. The results of the study showed that the different activities were satisfactory. The investigator believes that this improvised current balance apparatus could be further improved and modified.
Vita.
Thesis (M.A.T Physics)--University of the Philippines, Diliman.
Keywords: Magnetism; Scientific apparatus and instruments -- Philippines; Phyics -- Study and teaching -- Philippines